Impacts of risk based capital regulation in Malaysian Islamic insurers (Takaful) - Hui, Shan Lee; Cheng, Fan Fah; Md Nassir, Annuar; Ab Razak, Nazrul Hisyam (Universiti Sains Malaysia, 2019)
Risk Based Capital framework for Takaful operators (RBCT) is enforced by the Central Bank of Malaysia with the aim to ensure that Takaful operators have adequate capital to provide sound financial service. The objectives of this article is to examine the impacts of RBCT on efficiency, productivity and competitiveness level of Family Takaful Operators (FTO) and the relationship between efficiency and competitiveness in FTO in Malaysia. This study employs three methods namely Data Envelopment Analysis (DEA), Malmquist Productivity Index (MPI) and Panzar Rosse (PR) to investigate the impacts of RBC on the efficiency, productivity and competitiveness of FTO in Malaysia. The efficiency results indicate that after RBCT comes into effect, the cost efficiency has achieved higher efficient level. Although the productivity efficiency are improving, the technological systems of FTO are yet to achieve a reasonable level. From competitiveness results, the FTO are less competitive prior the implementation of RBCT, but has become more competitive after the regulation of RBCT framework. Furthermore, the more efficient of a Takaful market, the more competitive the market is. The implication of this study is that regulators need to impose prudent risk based capital regulation because it will improve the efficiency and competitiveness of Islamic insurers.